CULTURAL MANAGEMENT EDUCATION IN SOUTHEAST ASIA - Lim, Benny; Ser, Shaw Hong (International Journal of Indonesian Education and Teaching (IJIET), 2020)
Cultural Management could be defined as the process of planning, organizing, leading, and controlling material and nonmaterial culture to meet predetermined goals and objectives. Areas under the umbrella of Cultural Management include Arts Management, Museum Management, Culture Heritage and Tourism, Cultural and Creative Industries, and Design Management. Over the last two decades, there has also been a growing number of academic programmes befitting the umbrella of Cultural Management, offered at undergraduate and postgraduate levels by institutions of higher education in Southeast Asia. This paper explores the current state of Cultural Management education in Southeast Asia, and thereafter, highlights possible synergies to align with ASEAN’s agenda. Several qualitative research methods were adopted, including content analysis, followed by thematic analysis, participant observations, and semi-structured interviews. This paper formally documents and discusses the Cultural Management curriculum of 10 Southeast Asian nations, using three key themes - top-down, bottom-up, and a combination of both top-down and bottom-up focus. Thereafter, the paper proposes two ways in which institutions of higher education in Southeast Asia could better synergize to meet the six strategies listed in the ASEAN Strategic Plan for Culture and Arts 2016-2025.DOI: 10.24071/ijiet.2020.040102